2006
DOI: 10.4161/cbt.5.1.2347
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of a natural anthraquinone (Aloin) against human breast cancer cell lines with and without ErbB-2: Topoisomerase II-alpha coamplification

Abstract: In the present study the cytotoxic activity of aloin, a natural anthracycline from Aloe plant, is reported against two human breast cancer cell lines; without (MCF-7) and with (SKBR-3) erbB-2-topoIIα coamplification. MCF-7cell line was shown to be more sensitive to aloin than SKBR-3 demonstrated by MTT and clonogenic assays, from which IC 50 and 50% ICF values are reported to be 60 µg/ml, respectively, in the former cell line and as high as 150 and 80 µg/ml, respectively, in the latter, which are still far bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 32 publications
1
39
0
4
Order By: Relevance
“…Wang et al (2004) detectaram um efeito radio protetor da Aloe vera, em cultivo de células de pele humanas irradiadas e em camundongos, aumentando a sobrevivência de 10% para 86%. Em células humanas a Aloe vera foi testada por Esmat et al (2006) em cultivo celular de células humanas de câncer de mama. Eles demonstraram que essa planta reduziu as células mitóticas através da apoptose.…”
Section: Discussionunclassified
“…Wang et al (2004) detectaram um efeito radio protetor da Aloe vera, em cultivo de células de pele humanas irradiadas e em camundongos, aumentando a sobrevivência de 10% para 86%. Em células humanas a Aloe vera foi testada por Esmat et al (2006) em cultivo celular de células humanas de câncer de mama. Eles demonstraram que essa planta reduziu as células mitóticas através da apoptose.…”
Section: Discussionunclassified
“…Constitui-se principalmente por água e polissacarídeos, além de 70 outros componentes, tais como, vitamina A,B,C e E, cálcio, potássio, magnésio e zinco, diversos aminoácidos, enzimas e carboidratos. (Teske & Trentini, 1997;Femenia et al, 1999;Carvalho, 2005;Surjushe, 2008).…”
Section: Partes Utilizadas Na Terapêuticaunclassified
“…Uma das hipóteses levantadas é a de que há uma redução na proporção de células na fase mitótica por indução de apoptose provocada pelas antraquinonas (Esmat et al 2006).…”
Section: Atividade Antineoplásicaunclassified
“…In our in vitro study of aloin on human breast cancer cell lines, without (MCF-7) and with (SKBR-3) erbB-2-topoisomerase IIa co-amplification, we have shown that aloin at higher concentrations caused a reduction in the proportion of cells undergoing mitosis by induction of apoptosis, inhibition of topoisomerase IIa protein expression, and down-regulation of cyclin B1 protein expression in MCF-7, whereas erbB-2 protein expression was not affected. Topoisomerase IIa protein expression was mildly down-regulated in the SKBR-3 cell line at higher concentrations only (Esmat et al, 2006).…”
Section: Introductionmentioning
confidence: 97%